Bone Marrow Environment in Metastatic Neuroblastoma - Brignole, Chiara (Cancers (Basel), 2021)
SIMPLE SUMMARY: In children with metastatic neuroblastoma (NB) the overall survival is still poor despite aggressive multimodal therapies. Relapse and progression, which are the major causes of death, usually occur at the most common metastatic site, the bone marrow (BM). Thus, understanding the complex interaction between the BM-infiltrating NB cells and the BM environment may help identify the mechanisms that allow survival of the metastatic cells. Moreover, new therapeutics targeting the microenvironment and/or the resistance to treatment can lead to improved survival for these children. The complexity of the BM environment and the existence of multiple mechanisms, all favoring the escape of metastatic NB cells from immune recognition, stress the need to test synergistic immune therapy approaches. ABSTRACT: The study of the interactions occurring in the BM environment has been facilitated by the peculiar nature of metastatic NB. In fact: (i) metastases are present at diagnosis; (ii) metastases are confined in a very specific tissue, the BM, suggestive of a strong attraction and possibility of survival; (iii) differently from adult cancers, NB metastases are available because the diagnostic procedures require morphological examination of BM; (iv) NB metastatic cells express surface antigens that allow enrichment of NB metastatic cells by immune–magnetic separation; and (v) patients with localized disease represent an internal control to discriminate specific alterations occurring in the metastatic niche from generic alterations determined by the neoplastic growth at the primary site. Here, we first review the information regarding the features of BM-infiltrating NB cells. Then, we focus on the alterations found in the BM of children with metastatic NB as compared to healthy children and children with localized NB. Specifically, information regarding all the BM cell populations and their sub-sets will be first examined in the context of BM microenvironment in metastatic NB. In the last part, the information regarding the soluble factors will be presented.